Evaluation of side effect of risperidon on schizophrenic patient in Amino Gondohutomo hospital Semarang - M. Caecilia N Setiawati; Nanang Munif Yasin; Septiana Laksmi R (Indonesian Journal of Pharmacy, 2010)
Schizophrenia  is  a  psychiatrical  chronical  disease  of  human  being’s  mind which  can  influence  someone  so  that  it  bothered  the interpersonal  relation  and ability to have a social relationship. Antipsychotic drug can be used to overcome the  symptom of  schizophrenia, for  example risperidone.  This  study was  aims to evaluate the side effects of the use of risperidoneon the inpatient of Dr. Amino Gondohutomo  Mental  Hospital  Semarang  for  a  month  in the  period  of  February 2008.  This  evaluation  covers  the  side  effects  of  medicine  that  occur  due  to  the use  of  risperidone,  concomitant  administration  of  risperidone  and  other antipsychotic,  drug  interaction,and  also  executed  therapy  of  the  side  effects  of the  risperidone.  This  study  followed  the  descriptive  analysis,  while  the  data collecting  was  conducted  prospectively.  The  subjects  of  research  were represented  by  the  entire  patients  of  the  inpatient ward  of  Dr.  Amino Gondohutomo Mental Hospital Semarang during the period of February 2008 and fulfilled  the  inclusive  criteria.  The  inclusive  criteria  covered  the  patients  who were diagnosed as paranoid schizophrenia, hebephrenic schizophrenia, catatonic schizophrenia,  undetailed  schizophrenia  and  received  anti-psychotic  risperidone medication.  Based  on  these  criteria  31  samples  were found.  The  result  of  the study indicated that the most possibility of side effects of the use of risperidone was  agitation  (19.51  %),  with  the  most  anti-psychotic  combination  of risperidone  and  haloperidol  (45.83  %)  and  there  were  15  interactions  which could potentially cause a drug side effect.Key words: schizophrenia, drug side effects, anti-psychoticrisperidone